Les routes forestières au Québec : Les impacts environnementaux, sociaux et économiques - Laurence Bourgeois; Daniel Kneeshaw; Gaétane Boisseau (VertigO)
In Quebec, the kilometers of forest roads built per year are consistently increasing despite the fact that they have important ecological and socio-economic impacts. While such factors are being considered in the United States and other Canadian provinces, they remain ignored in Quebec. It is thus our goal to evaluate the effects of roads within a context applicable to Quebec and propose a series of solutions to those approaches used today. On an ecological scale, the effects of roads include the destruction and fragmentation of habitat, mortality due to vehicle collisions, animal behavioural changes, physical and chemical environmental changes, introduction of exotic species, and increased human access to the territory. Furthermore, opportunities for conservation are rendered difficult due to the rapid development of forest routes and the access they grant to intact, remote and unexploited territories. From a socio-economic perspective, the effects of roads are currently considered primarily for the economic interests of the government and forest industries. However, the vastness of the forest road network increases accessibility and can therefore create conflicts between various user groups thus complicating the management of forest resources. Cultural values, especially those of the indigenous communities are also at stake. From an economics point of view, it is important to integrate external costs and advantages tied to the various user groups in the territory and its resources in order to objectively and fairly assess priority activities whether they are ecologically, socially or culturally based. This would notably include the ecological role of the territory and the economic costs associated with the long term advantages of recreotourism. Among the suggested solutions, it appears imperative to reduce the construction of roads and protect those territories which remain intact. Different measures can also be proposed to diminish the effects of the existing road networks including: closing and reforesting certain routes, limiting access, constructing animal passages and ensuring habitat connectivity. Research and education programs should also be initiated in parallel to these measures as well as modifying political and governmental strategies and laws to target sustainable road management. Quebec is late in these initiatives and needs to take the necessary steps toward sustainable road management using as inspiration the strategies adopted elsewhere.